(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
During the Middle Ages, many scientists and thinkers lived and worked in Central Asia. Not only did they develop from the religious sciences, but they also created world-renowned scientific works in mathematics, philosophy, astronomy, medicine, pedagogy, anatomy, ethics and aesthetics, psychology, and so on. These works have been used not only by Central Asian readers, but also by progressive thinkers around the world.